Czytanie/mówienie/pisanie. Różewicz wobec oratury i tekstu (Czytanie książek z tomu "Płaskorzeźba") - Telicki, Marcin (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
Tadeusz Różewicz’s poem Czytanie książek (“The Reading of Books”) is part of a cycle of auto-thematic and self-referential works by the poet. The boundary between reality and literature is examined. I am discussing the problem of representation addressed by the author by categories of reading (making the starting point the ambiguity of the eponymous “reading”), orature and texture. Categories of orality and literacy, popularized by the anthropology of literature, applied to Czytanie książek facilitate a “close reading” and became a handy interpretive category. Hermeneutic problems caused by it (in understanding oneself, the world, and the text) some times confirm and sometimes modify the critical readings of Różewicz’s entire work.